Adhesive composition
By using a two-component epoxy-acrylic hybrid adhesive, combined with methacrylate monomer, low Tg toughening agent, phosphorus-containing compounds and free radical initiator, the problems of brittleness and low strength in high temperature and impact peeling tests are solved, and efficient room temperature curing and excellent performance at high temperatures are achieved.
Patent Information
- Application Number
- CN202380053348.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-14
- Filing Date
- 2023-06-02
- Publication Date
- 2025-02-28
AI Technical Summary
Existing epoxy-acrylic adhesives exhibit brittleness and low impact peel strength in high temperature and impact peel tests, which cannot meet the automotive industry's demand for heat resistance and impact peel strength.
Two-component epoxy-acrylic hybrid adhesives are employed, including methacrylate monomers, methacrylate end-tough toughener with low glass transition temperature (Tg), phosphorus-containing compounds and tertiary amine radical initiators, and epoxy resins and oxidants.
It achieves rapid curing at room temperature while maintaining excellent impact peel strength and overlap shear strength under high temperature conditions, and is suitable for applications that require heat resistance and high strength in the automotive industry.
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure QLYQS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the field of epoxy-acrylic adhesive compositions. Background Art
[0002] In the automotive industry, adhesives are used in the assembly of various components where they are bonded to each other or to other parts of the vehicle. During the assembly of closures (doors, hoods and decklids), some manufacturers require that the adhesives attain handling strength through a room temperature curing process 15 minutes before the parts enter the high temperatures of the electrophoretic coating ovens (which can cause partial deformation of panels that are not firmly bonded). During assembly of the vehicle, the bonded joints must also withstand the high temperatures of the paint and electrophoretic coating ovens.
[0003] Automobile manufacturers are increasingly looking at crimped flange joints as critical components in vehicle crashes. This is due to crash testing and real-world crash events where closures with adhesively bonded crimped flange joints have been untied or separated in high-speed crash events. Therefore, room temperature curing adhesives with heat resistance and impact peel strength are required for closure applications. Typically, the adhesive chemistry is an epoxy-acrylic hybrid in order to obtain fast cure and heat resistance. However, these systems are usually quite brittle and do not provide the required impact peel strength.
[0004] Historically, several classes of reactive and non-reactive toughening agents have been used in epoxy acrylic hybrid adhesives. One of the most effective and popular reactive toughening agents is methacrylate-terminated butadiene rubber or methacrylate-terminated butadiene acrylonitrile rubber. While this class of reactive toughening agents is very effective in imparting impact resistance, their supply chain position is very poor as there is only one source of their manufacturing in the world. In addition, the manufacture of these materials is hazardous and has negative environmental impacts.
[0005] There remains a need for acrylic-epoxy hybrid adhesives that exhibit good impact peel resistance after electrocoating exposure. Summary of the invention
[0006] In a first aspect, the present invention provides a two-component epoxy-acrylic hybrid adhesive comprising:
[0007] Part A
[0008] ai) at least one methacrylate monomer;
[0009] aii) at least one having a T of 0°C or less g A methacrylate-terminated toughening agent;
[0010] aiii) a phosphorus-containing compound selected from the group consisting of monoesters of phosphonic acid, monoesters and diesters of phosphonic acid and monoesters and diesters of phosphoric acid having one unit in which vinyl or allylic unsaturation is present;
[0011] aiv) tertiary amine free radical initiator;
[0012] Part B
[0013] bi) at least one epoxy resin;
[0014] bii) Oxidizing agents.
[0015] In a second aspect, the present invention provides a method for bonding two or more substrates, the method comprising the steps of:
[0016] (1) A two-component epoxy hybrid adhesive is provided, comprising:
[0017] Part A
[0018] ai) at least one methacrylate monomer;
[0019] aii) at least one having a T of 0°C or less g A methacrylate-terminated toughening agent;
[0020] aiii) a phosphorus-containing compound selected from the group consisting of monoesters of phosphonic acid, monoesters and diesters of phosphonic acid and monoesters and diesters of phosphoric acid having one unit in which vinyl or allylic unsaturation is present;
[0021] aiv) tertiary amine free radical initiator;
[0022] Part B
[0023] bi) at least one epoxy resin;
[0024] bii) oxidizing agents;
[0025] (2) mixing Part A and Part B to obtain an adhesive mixture;
[0026] (3) applying the adhesive mixture to the first substrate, the second substrate, or both;
[0027] (4) bringing the first substrate and the second substrate into bonding contact; and
[0028] (5) The adhesive mixture is cured. DETAILED DESCRIPTION
[0029] The inventors have discovered that it is possible to obtain epoxy-acrylic adhesives that have rapid cure at room temperature while having excellent impact peel strength even after exposure to elevated temperature conditions.
[0030] Definitions and Abbreviations
[0031] MDI 4,4'-methylenebis(phenyl isocyanate)
[0032] HDI Hexamethylene diisocyanate
[0033] HEMA Hydroxyethyl Methacrylate
[0034] IPDI Isophorone diisocyanate
[0035] PTMEG Poly(tetramethylene glycol)
[0036] PU Polyurethane
[0037] SEC Size Exclusion Chromatography
[0038] RH Relative humidity
[0039] CF Cohesive Failure
[0040] AF Bond Failure
[0041] M p Peak molecular weight, the molecular weight of the highest peak
[0042] FTIR Fourier Transform Infrared
[0043] DMA Dynamic Mechanical Analysis
[0044] Equivalent weights and molecular weights are measured by gel permeation chromatography (GPC) using the method and instrumentation listed in the Examples section.
[0045] At least one methacrylate monomer (ai)
[0046] Part A of the adhesive comprises at least one methacrylate monomer. There is no particular limitation on the methacrylate monomer. Examples include monomers having the general structure of Formula I:
[0047]
[0048] Wherein R is an organic group.
[0049] In a preferred embodiment, R is selected from H, C which may contain one or more heteroatoms. 1 -C 18 A substituted or unsubstituted cyclic or non-cyclic aliphatic hydrocarbon group, and a C 4 -C 18 Aromatic hydrocarbon group.
[0050] More preferably, R is selected from C 1 -C18 Substituted or unsubstituted cyclic or non-cyclic aliphatic hydrocarbon group, in particular, R is cyclohexyl or CH 2 -THF, wherein THF is 2- or 3-tetrahydrofurfuryl.
[0051] Other examples of methacrylate monomers include isobornyl methacrylate, cyclohexyl methacrylate, methyl methacrylate, and mixtures of these.
[0052] In some embodiments, part A comprises two or more methacrylate monomers.
[0053] In a preferred embodiment, part A comprises tetrahydrofurfuryl methacrylate (CAS [2455-24-5]).
[0054] In another preferred embodiment, part A comprises cyclohexyl methacrylate (CAS [101-43-9]).
[0055] In another preferred embodiment, part A comprises a divalent metal salt of methacrylic acid, in particular zinc dimethacrylate.
[0056] In a particularly preferred embodiment, part A comprises tetrahydrofurfuryl methacrylate and cyclohexyl methacrylate.
[0057] In another particularly preferred embodiment, part A comprises tetrahydrofurfuryl methacrylate, cyclohexyl methacrylate, and a divalent metal salt of methacrylic acid, in particular zinc dimethacrylate.
[0058] Based on the total weight of part A, the one or more methacrylate monomers preferably comprise 28-45 wt % of part A, more preferably 30-38 wt %.
[0059] In a preferred embodiment, part A comprises 25-35 wt%, more preferably 28-32 wt%, of tetrahydrofurfuryl methacrylate based on the total weight of part A.
[0060] In another preferred embodiment, part A comprises 2-10 wt %, more preferably 3-6 wt %, of cyclohexyl methacrylate based on the total weight of part A.
[0061] In another preferred embodiment, part A comprises 0.5-4 wt %, more preferably 0.75-1.5 wt %, of a divalent metal salt of methacrylic acid based on the total weight of part A.
[0062] In another preferred embodiment, part A comprises 0.5-4 wt %, more preferably 0.75-1.5 wt %, of zinc dimethacrylate based on the total weight of part A.
[0063] In a particularly preferred embodiment, part A comprises 25-35 wt%, more preferably 28-32 wt% of tetrahydrofurfuryl methacrylate, and 2-10 wt%, more preferably 3-6 wt% of cyclohexyl methacrylate, based on the total weight of part A.
[0064] In another particularly preferred embodiment, part A comprises 25-35 wt%, more preferably 28-32 wt% of tetrahydrofurfuryl methacrylate, 2-10 wt%, more preferably 3-6 wt% of cyclohexyl methacrylate, and 0.5-4 wt%, more preferably 0.75-1.5 wt% of zinc dimethacrylate, based on the total weight of part A.
[0065] At least one toughening agent (aii)
[0066] Part A comprises at least one having a T of 0°C or less g Methacrylate terminated toughening agent.
[0067] In a preferred embodiment, the toughening agent comprises at least one polyether as part of its backbone.
[0068] In a preferred embodiment, the toughening agent has a T of 120°C or less, more preferably -40°C or less. g .
[0069] In a preferred embodiment, at least one toughening agent comprises or consists of a toughening agent prepared by reacting a polyether polyol with a polyisocyanate in a ratio such that the resulting polymer is an NCO terminated polymer, followed by end-capping with a hydroxyalkyl methacrylate.
[0070] There is no particular limitation on the polyether polyol. The polyether polyol may be a diol or a triol, with a diol being preferred.
[0071] In a preferred embodiment, the polyol is poly(C 2 -C 6 -alkylene oxide) glycol, wherein C 2 , C 3 and C 4 is preferred, and C 4 Particularly preferred is [ie poly(tetramethylene glycol) or PTMEG].
[0072] In another preferred embodiment, the polyether polyol is selected from PTMEG having a molecular weight of 1,000 to 3,000 Da, more preferably 2,000 Da.
[0073] The toughening agent may also contain a low molecular weight (<250 Da) polyol having a functionality of 3 or 4, such as trimethylolpropane. If present, the low molecular weight polyol is preferably used at 0.1-3 wt%, more preferably 0.25-1 wt%, particularly preferably 0.5 wt%, based on the total weight of the toughening agent. In a preferred embodiment, the toughening agent contains 0.1-3 wt%, more preferably 0.25-1 wt%, particularly preferably 0.5 wt% of trimethylolpropane based on the total weight of the toughening agent.
[0074] There is no particular limitation on the polyisocyanate. The polyisocyanate may be aliphatic or aromatic, with aliphatic ones being preferred.
[0075] The polyisocyanate is preferably a diisocyanate.
[0076] In a preferred embodiment, the polyisocyanate is an aliphatic diisocyanate. Examples include hexamethylene diisocyanate (HDI), isophorone diisocyanate, methylene dicyclohexyl diisocyanate.
[0077] In a preferred embodiment, the polyether polyol is a diol and the polyisocyanate is a diisocyanate.
[0078] In another preferred embodiment, the polyether polyol is an aliphatic diol and the polyisocyanate is an aliphatic diisocyanate.
[0079] In another preferred embodiment, the polyether polyol is PTMEG and the polyisocyanate is HDI.
[0080] The hydroxyalkyl methacrylate is preferably C 2 -C 6 -hydroxyalkyl esters, more preferably C 2 -C 4 -hydroxyalkyl esters, even more preferably C 2 -C 3 -Hydroxyalkyl esters, wherein C 2 -Hydroxyalkyl esters are most preferred, especially hydroxyethyl methacrylate (HEMA):
[0081]
[0082] The toughening agent is preferably prepared by reacting a polyether polyol with a polyisocyanate in the presence of a polyurethane catalyst to produce an NCO-terminated prepolymer. The prepolymer is then reacted with a hydroxyalkyl methacrylate to result in end-capping.
[0083] In a preferred embodiment, the toughening agent is prepared by reacting PTMEG with HDI in the presence of a polyurethane catalyst to produce an NCO-terminated prepolymer. The prepolymer is then reacted with HEMA, resulting in end-capping. The resulting toughening agent has the general formula II:
[0084]
[0085] wherein x has a value of 13 to 42, more preferably 27.8 (this corresponds to a PTMEG molecular weight of 1,000 to 3,000 Da, more preferably 2,000 Da), and y has a value of 1.5 to 5 or 1.8 to 4.9, more preferably 2.6.
[0086] In a preferred embodiment, the toughening agent has the general formula II, having a number average molecular weight (M) of 6,119 Da. n ), as determined by gel permeation chromatography (GPC) according to the method described in the Examples section.
[0087] In a preferred embodiment, the toughening agent has the general formula II, PTMEG has a molecular weight of 2,000 Da, and the toughening agent has a number average molecular weight (M n ), as determined by gel permeation chromatography (GPC) according to the method described in the Examples section.
[0088] In a preferred embodiment, the toughening agent has the general formula II, having a weight average molecular weight (M) of 15,084 Da. w ), as determined by gel permeation chromatography (GPC) according to the method described in the Examples section.
[0089] In a preferred embodiment, the toughening agent has the general formula II, the PTMEG has a molecular weight of 2,000 Da, and the toughening agent has a weight average molecular weight (M w ), as determined by gel permeation chromatography (GPC) according to the method described in the Examples section.
[0090] In a preferred embodiment, part A comprises 10-30 wt %, more preferably 15-25 wt %, particularly preferably 17-22 wt %, of toughening agent (aii), based on the total weight of part A.
[0091] In another preferred embodiment, part A contains 10-30 wt%, more preferably 15-25 wt%, particularly preferably 17-22 wt% of a toughening agent (aii), based on the total weight of part A, wherein the toughening agent is prepared by reacting an aliphatic polyether diol with an aliphatic diisocyanate.
[0092] In another preferred embodiment, part A comprises 10-30 wt%, more preferably 15-25 wt%, particularly preferably 17-22 wt% of a toughening agent (aii), based on the total weight of part A, wherein the toughening agent is prepared by reacting an aliphatic polyether diol with an aliphatic diisocyanate, followed by reacting the aliphatic polyether diol with a C-type methacrylic acid. 2 -C 6 -hydroxyalkyl esters, more preferably C 2 -C 4 -hydroxyalkyl esters, even more preferably C 2 -C 3 -Hydroxyalkyl ester end-capping, wherein C 2 -Hydroxyalkyl esters are most preferred (hydroxyethyl methacrylate, HEMA).
[0093] In another preferred embodiment, part A comprises 10-30 wt%, more preferably 15-25 wt%, particularly preferably 17-22 wt% of a toughening agent (aii), based on the total weight of part A, wherein the toughening agent is prepared by reacting PTMEG with HDI, followed by reacting with methacrylic acid to form a toughening agent (aii). 2 -C 6 -hydroxyalkyl esters, more preferably C 2 -C 4 -hydroxyalkyl esters, even more preferably C 2 -C 3 -Hydroxyalkyl ester end-capping, wherein C 2 -Hydroxyalkyl esters are most preferred (hydroxyethyl methacrylate, HEMA).
[0094] In another preferred embodiment, part A comprises 10-30 wt%, more preferably 15-25 wt%, particularly preferably 17-22 wt% of a toughening agent (aii), based on the total weight of part A, wherein the toughening agent is prepared by reacting PTMEG with HDI and subsequently capping with HEMA.
[0095] In another preferred embodiment, part A comprises 10-30 wt%, more preferably 15-25 wt%, particularly preferably 17-22 wt% of a toughening agent (aii), wherein the toughening agent has formula II:
[0096]
[0097] wherein x has a value of 13 to 42, more preferably 27.73 (this corresponds to a PTMEG molecular weight of 1,000 to 3,000 Da, more preferably 2,000 Da), and y has a value of 1.5 to 5 or 1.8 to 4.9, more preferably 2.6.
[0098] Phosphorus-containing compounds (aiii)
[0099] Part A comprises a phosphorus-containing compound selected from monoesters of phosphonic acid having one unit in which vinyl or allylic unsaturation is present, monoesters and diesters of phosphonic acid and monoesters, diesters and triesters of phosphoric acid.
[0100] Preferably, the phosphorus-containing compound (aiii) has the formula III, IV and V:
[0101]
[0102] wherein W are the same or different and each W is independently selected from H and a divalent organic group, wherein at least one W is a divalent organic group, and at least one X is vinyl, and the other X is vinyl or absent (in the case where W is H), or H.
[0103] In another preferred embodiment, the phosphorus-containing compound (aiii) has Formula V.
[0104] In another preferred embodiment, the phosphorus-containing compound (aiii) has formula V, and one, two or three X groups are vinyl groups. Preferably, one X group is vinyl.
[0105] In another preferred embodiment, the phosphorus-containing compound (aiii) has formula V, and one, two or three WX groups have formula VI:
[0106]
[0107] Wherein the dot represents the point of free radical attachment. In the case where one or two WX groups have formula VI, the remaining WX groups are preferably H. In a particularly preferred embodiment, one WX group has formula VI and the remaining WX groups are H, resulting in formula VII:
[0108]
[0109] In another particularly preferred embodiment, two WX groups have formula VI, and the remaining WX groups are H, resulting in formula VIII:
[0110]
[0111] In another preferred embodiment, the phosphorus-containing compound (aiii) is an approximately 2:1 mixture of Formula VII and Formula VIII.
[0112] Other examples of phosphorus-containing compounds include, but are not limited to, phosphoric acid; 2-methacryloyloxyethyl phosphate; bis-(2-methacryloyloxyethyl) phosphate; 2-acryloyloxyethyl phosphate; bis-(2-acryloyloxyethyl) phosphate; methyl-(2-methacryloyloxyethyl) phosphate; ethyl methacryloyloxyethyl phosphate; methacryloyloxyethyl phosphate; ethyl acryloyloxyethyl phosphate; propyl acryloyloxyethyl phosphate, isobutyl acryloyloxyethyl phosphate, ethylhexyl acryloyloxyethyl phosphate, halogenated propyl acryloyloxyethyl phosphate, halogenated isobutyl acryloyloxyethyl phosphate, or halogenated ethylhexyl acryloyloxyethyl phosphate. Phosphoric acid; vinylphosphonic acid; cyclohexene-3-phosphonic acid; (α-hydroxybutylene-2-phosphonic acid; 1-hydroxy-1-phenylmethane-1,1-diphosphonic acid; 1-hydroxy-1-methyl-1-diphosphonic acid; 1-amino-1phenyl-1,1-diphosphonic acid; 3-amino-3-hydroxypropane-1,1-diphosphonic acid; amino-tri(methylenephosphonic acid); γ-amino-propylphosphonic acid; γ-glycidyloxypropylphosphonic acid; phosphoric acid-mono-2-aminoethyl ester; allylphosphonic acid; allylphosphinic acid; β-methacryloyloxyethylphosphinic acid; diallylphosphinic acid; β-methacryloyloxyethyl)phosphinic acid and allylmethacryloyloxyethylphosphinic acid. Preferred phosphorus compounds are 2-hydroxyethyl methacrylate phosphate and phosphonated (meth)acrylic acid monomers.
[0113] Tertiary amine free radical initiator (AIV)
[0114] Part A contains a tertiary amine free radical initiator. There is no particular limitation on the tertiary amine free radical initiator.
[0115] Preferred tertiary amine free radical initiators have the general formula IX:
[0116]
[0117] wherein W is selected from the group consisting of hydrogen, hydroxy, amino, halogen, alkyl having 1 to 8, preferably 1 to 4 carbon atoms, and alkoxy having 1 to 8, preferably 1 to 4 carbon atoms; R 1 and R 2 Independently selected from branched or straight chain C 1-4 -alkyl; and b is 1 or 2.
[0118] Examples include N,N-dimethylaniline, N,N-dimethylaminomethylphenol and N,N-dimethyl-p-toluidine.
[0119] In a particularly preferred embodiment, the tertiary amine free radical initiator is N,N-dimethyl-p-toluidine.
[0120] At least one epoxy resin (bi)
[0121] Part B comprises at least one epoxy resin.
[0122] Suitable epoxy resins include diglycidyl ethers of polyphenolic compounds (such as resorcinol, catechol, hydroquinone, bisphenol, bisphenol A, bisphenol AP (1,1-bis(4-hydroxyphenyl)-1-phenylethane), bisphenol F, bisphenol K, bisphenol M, tetramethylbiphenol), diglycidyl ethers of aliphatic diols and polyether diols (such as C 2-24 diglycidyl ethers of bisphenol A resins, such as those marketed by Olin Corporation under the name PANOL. 330, 331, 332, 383, 661 and 662 resin for sale.
[0123] In a preferred embodiment, the at least one epoxy resin comprises the reaction product of epichlorohydrin and bisphenol A.
[0124] In another preferred embodiment, the at least one epoxy resin comprises the liquid reaction product of epichlorohydrin and bisphenol A.
[0125] In a preferred embodiment, the at least one epoxy resin comprises an epoxy resin that is a liquid reaction product of epichlorohydrin and bisphenol A, the liquid reaction product having an epoxy equivalent weight of 182-192 g / equivalent (as measured according to ASTM D-1652), an epoxy percentage of 22.4%-23.6% (as measured according to ASTM D-1652), an epoxy group content of 5,200-5,500 mmol / kg (as measured according to ASTM D-1652), and a viscosity of 11,000-14,000 mPas at 25° C. (as measured according to ASTM D-445).
[0126] In another preferred embodiment, the at least one epoxy resin comprises a bisphenol A-based epoxy resin having an epoxy equivalent weight of about 352.5 g / equivalent.
[0127] In a particularly preferred embodiment, the at least one epoxy resin comprises a mixture of a liquid reaction product of epichlorohydrin and bisphenol A and a bisphenol A-based epoxy resin having an epoxy equivalent weight of about 352.5 g / equivalent, the liquid reaction product having an epoxy equivalent weight of 182-192 g / equivalent (as measured according to ASTM D-1652), an epoxy percentage of 22.4%-23.6% (as measured according to ASTM D-1652), an epoxy group content of 5,200-5,500 mmol / kg (as measured according to ASTM D-1652), and a viscosity of 11,000-14,000 mPas at 25° C. (as measured according to ASTM D-445).
[0128] In a preferred embodiment, the at least one epoxy resin comprises 50-90 wt%, more preferably 60-80 wt%, based on the total weight of the epoxy resins in part B, of a liquid reaction product of epichlorohydrin and bisphenol A, the liquid reaction product having an epoxy equivalent weight of 182-192 g / equivalent (as measured according to ASTM D-1652), an epoxy percentage of 22.4%-23.6% (as measured according to ASTM D-1652), an epoxy group content of 5,200-5,500 mmol / kg (as measured according to ASTM D-1652), and a viscosity of 11,000-14,000 mPas at 25° C. (as measured according to ASTM D-445).
[0129] In another preferred embodiment, the at least one epoxy resin comprises 10-50 wt%, more preferably 20-40 wt%, of a bisphenol A-based epoxy resin having an epoxy equivalent weight of about 352.5 g / equivalent, based on the total weight of the epoxy resins in Part B.
[0130] In another preferred embodiment, the at least one epoxy resin comprises 50-90 wt%, more preferably 60-80 wt%, of a liquid reaction product of epichlorohydrin and bisphenol A, based on the total weight of the epoxy resins in part B, and 10-50 wt%, more preferably 20-40 wt%, of a bisphenol A-based epoxy resin having an epoxy equivalent weight of about 352.5 g / equivalent, the liquid reaction product having an epoxy equivalent weight of 182-192 g / equivalent (as measured according to ASTM D-1652), an epoxy percentage of 22.4%-23.6% (as measured according to ASTM D-1652), an epoxy group content of 5,200-5,500 mmol / kg (as measured according to ASTM D-1652), and a viscosity of 11,000-14,000 mPas at 25° C. (as measured according to ASTM D-445).
[0131] Part B preferably comprises 20 to 80 wt %, more preferably 20 to 60 wt %, very particularly preferably 25 to 40 wt %, of at least one epoxy resin, based on the total weight of part B.
[0132] Oxidant (bii)
[0133] Part B contains an oxidizing agent. There is no particular limitation on the oxidizing agent.
[0134] Representative oxidants include, but are not limited to, organic peroxides such as benzoyl peroxide and other diacyl peroxides, hydroperoxides such as cumene hydroperoxide, peresters such as β-butyl peroxybenzoate; ketone hydroperoxides such as methyl ethyl ketone hydroperoxide, organic salts of transition metals such as cobalt naphthenate, and labile chlorine-containing compounds such as sulfonyl chloride. The most preferred oxidant is benzoyl peroxide.
[0135] The oxidizing agent, preferably an organic peroxide, is preferably present in part B at 3-10 wt %, based on the total weight of part B, more preferably 5-9 wt %.
[0136] In a preferred embodiment, part B comprises 3-10 wt %, more preferably 5-9 wt %, of benzoyl peroxide based on the total weight of part B.
[0137] Optional Ingredients
[0138] The adhesive of the present invention may contain additional optional ingredients such as, for example:
[0139] Stabilizers / radical scavengers may be added to both Part A and Part B to extend the shelf life of the unmixed parts. Examples of stabilizers / radical scavengers include 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, diethylhydroxylamine (DEHA), butylated hydroxytoluene (BHT), methyl ether of hydroquinone, hydroquinone, benzoquinone, naphthoquinone, hydroxylamine, and nitrile oxide.
[0140] Fillers such as wollastonite, talc, fumed silica, calcium carbonate and glass.
[0141] Part A may optionally comprise a crosslinking agent, such as a divalent metal salt of methacrylic acid, such as zinc dimethacrylate, calcium dimethacrylate, magnesium dimethacrylate, or mixtures of these.
[0142] Part A may optionally contain additional toughening agents. Suitable additional toughening agents are rubber-based, such as acrylate-based toughening agents, butadiene-based toughening agents, acrylonitrile-butadiene-based toughening agents, chlorinated or chlorosulfonated polyethylene, block copolymers of styrene and conjugated dienes (SBS, SIS), ethylene acrylic elastomers, core-shell graft copolymers.
[0143] In a preferred embodiment, part A comprises a rubber-based toughening agent.
[0144] In another preferred embodiment, part A comprises a rubber-based toughener selected from acrylate-based tougheners, butadiene-based tougheners, acrylonitrile-butadiene-based tougheners, chlorinated or chlorosulfonated polyethylene, block copolymers of styrene and conjugated dienes (SBS, SIS), ethylene acrylic elastomers, and core-shell graft copolymers.
[0145] In another preferred embodiment, part A comprises a rubber-based toughening agent which is a copolymer of methyl 2-methyl-2-acrylate and 1,3-butadiene.
[0146] If used, additional rubber-based toughening agents are preferably used in part A at 2-24 wt%, based on the total weight of part A, more preferably 7.5-18.5 wt%, and even more preferably 10-15.75 wt%.
[0147] In a preferred embodiment, part A comprises a rubber-based toughening agent, which is used in an amount of 2-24 wt %, more preferably 7.5-18.5 wt %, and more preferably 10-15.75 wt %, based on the total weight of part A.
[0148] In another preferred embodiment, part A contains a rubber-based toughener, which is selected from acrylate-based tougheners, butadiene-based tougheners, acrylonitrile-butadiene-based tougheners, chlorinated or chlorosulfonated polyethylene, block copolymers of styrene and conjugated dienes (SBS, SIS), ethylene acrylic elastomers, core-shell graft copolymers, and is used in an amount of 2-24 wt%, more preferably 7.5-18.5 wt%, and more particularly preferably 10-15.75 wt%, based on the total weight of part A.
[0149] In another preferred embodiment, part A comprises a rubber-based toughening agent which is a copolymer of methyl 2-methyl-2-acrylate and 1,3-butadiene, used at 2-24 wt%, more preferably 7.5-18.5 wt%, and more particularly preferably 10-15.75 wt%, based on the total weight of part A.
[0150] Additional optional ingredients may include, for example, adhesion promoters, pigments, thixotropic agents, wetting agents, reactive diluents, antioxidants, inhibitors, and stabilizers.
[0151] Manufacturing method
[0152] At least one toughening agent is produced by a process comprising the steps of:
[0153] (1) mixing polyether polyol and polyisocyanate;
[0154] (2) adding a catalyst capable of catalyzing the reaction of hydroxyl groups with isocyanate groups to form an isocyanate-terminated prepolymer; and
[0155] (3) The isocyanate prepolymer is then reacted with a hydroxyalkyl methacrylate so that the isocyanate groups are terminated with the hydroxyalkyl methacrylate.
[0156] The reactions in steps (2) and (3) are typically carried out under vacuum or under a neutral atmosphere such as nitrogen or argon.
[0157] Preferred polyether polyols are as listed under the description of toughening agents.
[0158] Preferred polyisocyanates are as listed under the description of toughening agents.
[0159] Preferred hydroxyalkyl methacrylates are as listed under the description of toughening agents.
[0160] The catalyst is preferably selected from Lewis bases and Lewis acids. Suitable catalysts include tertiary amines, including diazabicyclo[2.2.2]octane, 2,4,6-tris((dimethylamino)methyl)phenol, DMDEE (2,2'-dimorpholinodiethyl ether), imidazoles, such as 4-methylimidazole, triethanolamine and organometallic catalysts, in particular organotin compounds, such as dibutyltin dilaurate, dioctyltin dineodecanoate and other metal catalysts, such as tetrabutyl titanate, zirconium acetylacetonate and bismuth neodecanoate.
[0161] Dibutyltin dilaurate is particularly preferred.
[0162] How to use
[0163] In use, the adhesive parts A and B are mixed until homogeneous and applied immediately. The mixing ratio of part A to part B is preferably 2:1 to 10:1, with 3:1 being particularly preferred.
[0164] Suitable substrates include, for example, electrogalvanized steel, hot-dip galvanized steel, cold rolled steel, aluminum.
[0165] Effects of the Invention
[0166] The adhesives of the present invention exhibit good impact peel strength, particularly when measured according to ISO 11343.
[0167] In a preferred embodiment, the adhesive exhibits an impact peel strength of at least 15 N / mm, more preferably at least 20 N / mm, when measured according to ISO 11343 using electrogalvanized steel as the substrate at a bonding area of 20X30 mm and a bonding gap of 10 mils and cured at 23°C for 1 day followed by curing at 190°C for 45 minutes.
[0168] When tested according to ISO 11343 on electrogalvanized steel after curing for 1 day at 23°C followed by 45 minutes at 190°C, the adhesive of the invention preferably exhibits a cohesive failure mode of at least 90%.
[0169] The adhesives of the present invention preferably exhibit a lap shear strength of at least 10 MPa, more preferably at least 11 MPa, when measured in accordance with ISO 4587 using electrogalvanized steel as the substrate with a 1 / 2 square inch overlap as the bond area, a 10 mil bond gap, and cured for 16 hours at 23°C and 45 minutes at 190°C.
[0170] When tested according to ISO 4587 on electrogalvanized steel after curing at 23°C for 16 hours followed by curing at 190°C for 45 minutes, the adhesive of the present invention preferably exhibits a cohesive failure mode of at least 90%.
[0171] application
[0172] The adhesives of the present invention are particularly useful in automotive applications where a relatively rapid cure is required and where the bonded parts will subsequently be exposed to electrocoating conditions.
[0173] Particularly preferred embodiments
[0174] The following are particularly preferred embodiments of the present invention:
[0175] 1. A two-component epoxy-acrylic hybrid adhesive comprising:
[0176] Part A
[0177] ai) at least one methacrylate monomer;
[0178] aii) at least one having a T of 0°C or less g A methacrylate-terminated toughening agent;
[0179] aiii) a phosphorus-containing compound selected from the group consisting of monoesters of phosphonic acid, monoesters and diesters of phosphonic acid and monoesters and diesters of phosphoric acid having one unit in which vinyl or allylic unsaturation is present;
[0180] aiv) tertiary amine free radical initiator;
[0181] Part B
[0182] bi) at least one epoxy resin;
[0183] bii) Oxidizing agents.
[0184] 2. A method for bonding two or more substrates, the method comprising the steps of:
[0185] (1) A two-component epoxy hybrid adhesive is provided, comprising:
[0186] Part A
[0187] ai) at least one methacrylate monomer;
[0188] aii) at least one having a T of 0°C or less g A methacrylate-terminated toughening agent;
[0189] aiii) a phosphorus-containing compound selected from the group consisting of monoesters of phosphonic acid, monoesters and diesters of phosphonic acid and monoesters and diesters of phosphoric acid having one unit in which vinyl or allylic unsaturation is present;
[0190] aiv) tertiary amine free radical initiator;
[0191] Part B
[0192] bi) at least one epoxy resin;
[0193] bii) oxidizing agents;
[0194] (2) mixing Part A and Part B to obtain an adhesive mixture;
[0195] (3) applying the adhesive mixture to the first substrate, the second substrate, or both;
[0196] (4) bringing the first substrate and the second substrate into bonding contact; and
[0197] (5) The adhesive mixture is cured.
[0198] 3. As described in embodiment 1 or 2, wherein the at least one toughening agent has a T of -20°C or less when measured by DMA. g .
[0199] 4. As described in embodiment 1, 2 or 3, wherein the toughening agent has a T of -40°C or less when measured by DMA. g .
[0200] 5. As described in any preceding embodiment, the at least one toughening agent comprises or consists of a toughening agent prepared by reacting a polyether polyol with a polyisocyanate followed by end-capping with a hydroxyalkyl methacrylate.
[0201] 6. As described in any preceding embodiment, wherein the at least one methacrylate monomer (ai) comprises a molecule having the general structure of I:
[0202]
[0203] Wherein R is an organic group.
[0204] 7. As described in any preceding embodiment, wherein part A additionally comprises one or more divalent metal salts of methacrylic acid, preferably zinc dimethacrylate.
[0205] 8. As described in Example 6, wherein R is selected from H, C which may contain one or more heteroatoms 1 -C 18 A substituted or unsubstituted cyclic or non-cyclic aliphatic hydrocarbon group, and a C 4 -C 18 Aromatic hydrocarbon group.
[0206] 9. As described in Example 6, wherein R is selected from C which may contain one or more heteroatoms 1 -C 18 Substituted or unsubstituted cyclic or non-cyclic aliphatic hydrocarbon group, in particular, R is cyclohexyl or CH 2 -THF, wherein THF is 2- or 3-tetrahydrofurfuryl.
[0207] 10. As described in any preceding embodiment, wherein part A comprises two or more methacrylate monomers.
[0208] 11. As described in any preceding embodiment, wherein the at least one methacrylate monomer comprises tetrahydrofurfuryl methacrylate.
[0209] 12. As described in any preceding embodiment, wherein the at least one methacrylate monomer comprises cyclohexyl methacrylate.
[0210] 13. As described in any preceding embodiment, wherein part A additionally comprises a divalent metal salt of methacrylic acid, in particular zinc dimethacrylate.
[0211] 14. As described in any preceding embodiment, wherein the at least one methacrylate monomer comprises tetrahydrofurfuryl methacrylate and cyclohexyl methacrylate.
[0212] 15. As described in any preceding embodiment, wherein the at least one methacrylate monomer comprises tetrahydrofurfuryl methacrylate and cyclohexyl methacrylate.
[0213] 16. As described in any preceding embodiment, wherein the one or more methacrylate monomers represent 25-35 wt%, more preferably 28-32 wt%, of tetrahydrofurfuryl methacrylate based on the total weight of Part A.
[0214] 17. As described in any preceding embodiment, wherein part A comprises 25-35 wt%, more preferably 28-32 wt%, of tetrahydrofurfuryl methacrylate based on the total weight of part A.
[0215] 18. As described in any preceding embodiment, wherein part A comprises 2-10 wt%, more preferably 3-6 wt%, of cyclohexyl methacrylate based on the total weight of part A.
[0216] 19. As described in any preceding embodiment, wherein part A comprises 0.5-4 wt %, more preferably 0.75-1.5 wt %, of the divalent metal salt of methacrylic acid based on the total weight of part A.
[0217] 20. As described in any preceding embodiment, wherein part A comprises 0.5-4 wt %, more preferably 0.75-1.5 wt %, of zinc dimethacrylate based on the total weight of part A.
[0218] 21. As described in any of the preceding embodiments, wherein part A comprises 25-35 wt%, more preferably 28-32 wt% of tetrahydrofurfuryl methacrylate, and 2-10 wt%, more preferably 3-6 wt% of cyclohexyl methacrylate, based on the total weight of part A.
[0219] 22. As described in any of the preceding embodiments, part A comprises 25-35 wt%, more preferably 28-32 wt% of tetrahydrofurfuryl methacrylate, 2-10 wt%, more preferably 3-6 wt% of cyclohexyl methacrylate, and 0.5-4 wt%, more preferably 0.75-1.5 wt% of zinc dimethacrylate, based on the total weight of part A.
[0220] 23. As described in any preceding embodiment, the polyether polyol used to prepare the toughening agent is a diol or a triol.
[0221] 24. As described in any preceding embodiment, the polyether polyol used to prepare the toughening agent is a diol.
[0222] 25. As described in any of the preceding embodiments, the polyether polyol used to prepare the toughening agent is poly(C 2 -C 6 -alkylene oxide) glycol, wherein C 2 , C 3 and C 4 is preferred, and C 4 Particularly preferred is [ie poly(tetramethylene glycol) or PTMEG].
[0223] 26. As described in any of the preceding embodiments, the polyether polyol used to prepare the toughening agent is selected from PTMEG with a molecular weight of 1,000 to 3,000 Da, more preferably 2,000 Da.
[0224] 27. As described in any preceding embodiment, wherein the polyisocyanate used to prepare the toughening agent is aliphatic or aromatic.
[0225] 28. As described in any preceding embodiment, wherein the polyisocyanate used to prepare the toughening agent is aliphatic.
[0226] 29. As described in any preceding embodiment, wherein the polyisocyanate used to prepare the toughening agent is a diisocyanate.
[0227] 30. As described in any preceding embodiment, the polyisocyanate used to prepare the toughening agent is selected from hexamethylene diisocyanate (HDI), isophorone diisocyanate, and methylene dicyclohexyl diisocyanate.
[0228] 31. As described in any preceding embodiment, wherein the polyether polyol used to prepare the toughening agent is PTMEG, and the polyisocyanate is HDI.
[0229] 32. As described in any of the preceding embodiments, wherein the hydroxyalkyl methacrylate used to prepare the toughening agent is C 2 -C 6 -Hydroxyalkyl esters.
[0230] 33. As described in any of the preceding embodiments, wherein the hydroxyalkyl methacrylate used to prepare the toughening agent is C 2 -C 4 -Hydroxyalkyl esters.
[0231] 34. As described in any of the preceding embodiments, wherein the hydroxyalkyl methacrylate used to prepare the toughening agent is C 2 -C 3 -Hydroxyalkyl esters.
[0232] 35. As described in any of the preceding embodiments, wherein the hydroxyalkyl methacrylate used to prepare the toughening agent is hydroxyethyl methacrylate (HEMA):
[0233]
[0234] 36. As described in any of the preceding embodiments, wherein the toughening agent has the general formula II:
[0235]
[0236] where x has values from 13 to 42.
[0237] 37. As described in embodiment 36, wherein x is 27.8.
[0238] 38. As described in embodiment 36 or 37, wherein y has a value of 1.5 to 5.
[0239] 39. As described in any one of embodiments 36 to 38, wherein y has a value of 1.8 to 4.9.
[0240] 40. As described in any one of embodiments 36 to 39, wherein y is 2.6.
[0241] 41. As described in any of the preceding embodiments, wherein the toughening agent has the general formula II and has a number average molecular weight (M) of 6,119 Da. n ), as determined by gel permeation chromatography (GPC) according to the method described in the Examples section.
[0242] 42. As described in any of the preceding embodiments, wherein the toughening agent has the general formula II and has a weight average molecular weight (M) of 15,084 Da. w ), as determined by gel permeation chromatography (GPC) according to the method described in the Examples section.
[0243] 43. As described in any preceding embodiment, wherein part A comprises 10-30 wt% of the toughening agent (aii) based on the total weight of part A.
[0244] 44. As described in any preceding embodiment, part A comprises 15-25 wt% of the toughening agent (aii) based on the total weight of part A.
[0245] 45. As described in any preceding embodiment, wherein part A comprises 17-22 wt% of the toughening agent (aii) based on the total weight of part A.
[0246] 46. As described in any of the preceding embodiments, wherein the phosphorus-containing compound (aiii) has Formula III, IV and V:
[0247]
[0248] wherein W are the same or different and each W is independently selected from H and a divalent organic group, wherein at least one W is a divalent organic group, and at least one X is vinyl, and the other X is vinyl or absent (in the case where W is H), or H.
[0249] 47. As described in any preceding embodiment, wherein the phosphorus-containing compound (aiii) has formula V.
[0250] 48. As described in any preceding embodiment, wherein the phosphorus-containing compound (aiii) has formula V, and one, two or three X groups are vinyl groups.
[0251] 49. As described in any preceding embodiment, wherein the phosphorus-containing compound (aiii) is of formula V, and an X group is vinyl.
[0252] 50. As described in any of the preceding embodiments, wherein the phosphorus-containing compound (aiii) has formula V, and one, two or three WX groups have formula VI:
[0253]
[0254] The dots represent the points of free radical attachment.
[0255] 51. As described in embodiment 50, one or two WX groups have formula VI and the remaining WX groups are H.
[0256] 52. As described in any of the preceding embodiments, wherein the phosphorus-containing compound comprises a molecule of formula VII:
[0257]
[0258] 53. As described in any preceding embodiment, wherein the phosphorus-containing compound comprises a molecule of Formula VIII:
[0259]
[0260] 54. As described in any preceding embodiment, wherein the phosphorus-containing compound (aiii) is about a 2:1 mixture of Formula VII and Formula VIII.
[0261] 55. As described in any preceding embodiment, wherein the tertiary amine free radical initiator is N,N-dimethyl-p-toluidine.
[0262] 56. As described in any preceding embodiment, the at least one epoxy resin comprises a diglycidyl ether of a polyphenol compound.
[0263] 57. As described in any preceding embodiment, the at least one epoxy resin comprises the reaction product of bisphenol A and epichlorohydrin.
[0264] 58. As described in any preceding embodiment, the at least one epoxy resin comprises a liquid reaction product of bisphenol A and epichlorohydrin.
[0265] 59. As described in any preceding embodiment, wherein the at least one epoxy resin comprises a liquid reaction product of epichlorohydrin and bisphenol A, the liquid reaction product having an epoxy equivalent weight of 182-192 g / equivalent (as measured according to ASTM D-1652), an epoxy percentage of 22.4%-23.6% (as measured according to ASTM D-1652), an epoxy group content of 5,200-5,500 mmol / kg (as measured according to ASTM D-1652), and a viscosity of 11,000-14,000 mPas at 25° C. (as measured according to ASTM D-445).
[0266] 60. As described in any preceding embodiment, the at least one epoxy resin comprises a bisphenol A-based epoxy resin having an epoxy equivalent weight of about 352.5 g / equivalent.
[0267] 61. As described in any preceding embodiment, the at least one epoxy resin comprises a mixture of a liquid reaction product of epichlorohydrin and bisphenol A and a bisphenol A-based epoxy resin having an epoxy equivalent weight of about 352.5 g / equivalent, the liquid reaction product having an epoxy equivalent weight of 182-192 g / equivalent (as measured according to ASTM D-1652), an epoxy percentage of 22.4%-23.6% (as measured according to ASTM D-1652), an epoxy group content of 5,200-5,500 mmol / kg (as measured according to ASTM D-1652), and a viscosity of 11,000-14,000 mPas at 25° C. (as measured according to ASTM D-445).
[0268] 62. As described in any of the preceding embodiments, the at least one epoxy resin comprises 50-90 wt%, more preferably 60-80 wt%, based on the total weight of the epoxy resins in part B, of a liquid reaction product of epichlorohydrin and bisphenol A, the liquid reaction product having an epoxy equivalent weight of 182-192 g / equivalent (as measured according to ASTM D-1652), an epoxy percentage of 22.4%-23.6% (as measured according to ASTM D-1652), an epoxy group content of 5,200-5,500 mmol / kg (as measured according to ASTM D-1652), and a viscosity of 11,000-14,000 mPas at 25° C. (as measured according to ASTM D-445).
[0269] 63. As described in any preceding embodiment, the at least one epoxy resin comprises 10-50 wt%, more preferably 20-40 wt%, of a bisphenol A-based epoxy resin having an epoxy equivalent weight of about 352.5 g / equivalent, based on the total weight of the epoxy resins in Part B.
[0270] 64. As described in any preceding embodiment, the at least one epoxy resin comprises 50-90 wt%, more preferably 60-80 wt%, of a liquid reaction product of epichlorohydrin and bisphenol A, based on the total weight of the epoxy resins in part B, and 10-50 wt%, more preferably 20-40 wt%, of a bisphenol A-based epoxy resin with an epoxy equivalent weight of about 352.5 g / equivalent, the liquid reaction product having an epoxy equivalent weight of 182-192 g / equivalent (as measured according to ASTM D-1652), an epoxy percentage of 22.4%-23.6% (as measured according to ASTM D-1652), an epoxy group content of 5,200-5,500 mmol / kg (as measured according to ASTM D-1652), and a viscosity of 11,000-14,000 mPas at 25° C. (as measured according to ASTM D-445).
[0271] 65. As described in any preceding embodiment, wherein Part B comprises at least one epoxy resin in an amount of 20 to 80 wt %, more preferably 20 to 60 wt %, and even more preferably 25 to 40 wt % of the epoxy resin, based on the total weight of Part B.
[0272] 66. As described in any preceding embodiment, wherein the oxidizing agent is an organic peroxide.
[0273] 67. As described in any of the preceding embodiments, the oxidizing agent is selected from benzoyl peroxide and other diacyl peroxides, hydroperoxides such as cumene hydroperoxide, peresters such as β-butyl peroxybenzoate; ketone hydroperoxides such as methyl ethyl ketone hydroperoxide, organic salts of transition metals such as cobalt naphthenate, and labile chlorine-containing compounds such as sulfonyl chloride.
[0274] 68. As described in any preceding embodiment, wherein the organic peroxide is benzoyl peroxide.
[0275] 69. As described in any preceding embodiment, the organic peroxide is present in part B at 3-10 wt %, more preferably 5-9 wt %, based on the total weight of part B.
[0276] 70. As described in any preceding embodiment, wherein part B comprises 3-10 wt %, more preferably 5-9 wt %, of benzoyl peroxide based on the total weight of part B.
[0277] 71. As described in any preceding embodiment, wherein part A and / or part B comprises a stabilizer and / or a free radical stabilizer.
[0278] 72. As described in any of the preceding embodiments, part A and / or part B comprises a stabilizer and / or a free radical scavenger selected from 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, diethylhydroxylamine (DEHA), butylated hydroxytoluene (BHT), and mixtures thereof.
[0279] 73. As described in any preceding embodiment, wherein part A and / or part (B) comprises a filler selected from the group consisting of wollastonite, talc, fumed silica, calcium carbonate, and mixtures thereof.
[0280] 74. As described in any preceding embodiment, wherein part A comprises an additional toughening agent.
[0281] 75. As described in any of the preceding embodiments, part A comprises an additional toughening agent, which is rubber-based, such as acrylate-based toughening agents, butadiene-based toughening agents, acrylonitrile-butadiene-based toughening agents, chlorinated or chlorosulfonated polyethylene, block copolymers of styrene and conjugated dienes (SBS, SIS), ethylene acrylic elastomers, and core-shell graft copolymers.
[0282] 76. Any preceding embodiment, wherein part A additionally comprises a rubber-based toughening agent.
[0283] 77. As described in any of the preceding embodiments, part A additionally comprises a rubber-based toughener selected from acrylate-based tougheners, butadiene-based tougheners, acrylonitrile-butadiene-based tougheners, chlorinated or chlorosulfonated polyethylene, block copolymers of styrene and conjugated dienes (SBS, SIS), ethylene acrylic elastomers, and core-shell graft copolymers.
[0284] 77. As described in any preceding embodiment, wherein part A additionally comprises a rubber-based toughening agent, the rubber-based toughening agent being a copolymer of methyl 2-methyl-2-acrylate and 1,3-butadiene.
[0285] 78. As described in any preceding embodiment, the additional rubber-based toughening agent is used in part A at 2-24 wt%, more preferably 7.5-18.5 wt%, and more preferably 10-15.75 wt%, based on the total weight of part A.
[0286] 79. As described in any of the preceding embodiments, part A additionally comprises a rubber-based toughening agent, which is used in an amount of 2-24 wt %, more preferably 7.5-18.5 wt %, and even more preferably 10-15.75 wt %, based on the total weight of part A.
[0287] 80. As described in any of the preceding embodiments, part A additionally comprises a rubber-based toughener, which is selected from acrylate-based tougheners, butadiene-based tougheners, acrylonitrile-butadiene-based tougheners, chlorinated or chlorosulfonated polyethylene, block copolymers of styrene and conjugated dienes (SBS, SIS), ethylene acrylic elastomers, and core-shell graft copolymers, and is used in an amount of 2-24 wt%, more preferably 7.5-18.5 wt%, and more particularly preferably 10-15.75 wt%, based on the total weight of part A.
[0288] 81. As described in any of the preceding embodiments, part A comprises a rubber-based toughening agent, which is a copolymer of methyl 2-methyl-2-acrylate and 1,3-butadiene, used in an amount of 2-24 wt%, more preferably 7.5-18.5 wt%, and more preferably 10-15.75 wt%, based on the total weight of part A.
[0289] Examples
[0290] The ingredients are listed in Table 1.
[0291]
[0292]
[0293]
[0294]
[0295]
[0296] Preparation of toughening agent 1
[0297] The toughening agents were prepared using the ingredients listed in Table 2.
[0298]
[0299] Components 1 and 2 (PTMEG and trimethylolpropane) were added to the reactor and heated to 120°C under vacuum while stirring. Stirring was continued for 30 minutes. The reactor was cooled to 60°C and component 3 (1,6-HDI) was added. Mixing was continued for two minutes. Component 4 (DBTL) was added and mixing was continued for 40 minutes. The NCO content was determined by FTIR to be 3.5 wt%.
[0300] Component 5 (BHT) was added and mixing was continued for 20 minutes, and the mixture was cooled to 50° C. Component 6 (HEMA) was added and the mixture was mixed for 40 minutes. The NCO content was determined by FTIR to be about 0.
[0301] The number average molecular weight (M) was determined by GPC. n ) was 6,119 Da, and the weight average molecular weight (M w ) is 15,084 Da.
[0302] The GPC method used was as follows:
[0303] The toughener of aliquot (0.4991 g) is weighed into a 16-mL screw-cap glass vial equipped with a screw cap of a Teflon liner using an analytical balance (Sartorius, model 1702). 10 mL of tetrahydrofuran (THF, Baker Analyzed, HPLC solvent, low water) is transferred to a glass vial using a 10-mL transfer pipette. Contents are fully mixed using a vortex mixer (Scientific Industries, Inc., Vortex Genie 2, model G-560). The solution of about 1.5 mL is then transferred to an autosampler vial for GPC analysis.
[0304] Molecular Weight Calibration Standards:
[0305] Calibration Standard 1:
[0306] The following narrow molecular weight distribution polymer standards were weighed into 25 mL screw-top glass vials equipped with Teflon-lined screw caps using an analytical balance:
[0307] PS, M p =139,400 (0.0522 g); polystyrene, M p =32,300 (0.0628 g); polyethylene glycol, M p =3,140 (0.0735 g); polyethylene glycol, M p =600 (0.0853 g); polyethylene glycol, M p =180(0.1038g).
[0308] Use a 25-mL pipette to add 25 mL of THF to the glass vial. Mix the solution thoroughly with a vortex mixer. Then transfer approximately 1.5 mL of the solution to the autosampler vial for GPC analysis.
[0309] Calibration Standard 2:
[0310] The following narrow molecular weight distribution polymer standards were weighed into 25 mL screw-top glass vials equipped with Teflon-lined screw caps using an analytical balance:
[0311] PS, M p=568,700 (0.0506 g); polystyrene, M p =61,600 (0.0608 g); polyethylene glycol, M p =7,750 (0.0757 g); polyethylene glycol, M p =970 (0.0828 g); polyethylene glycol, M p =400(0.1019g).
[0312] Use a 25-mL pipette to add 25 mL of THF to the glass vial. Mix the solution thoroughly with a vortex mixer. Then transfer approximately 1.5 mL of the solution to the autosampler vial for GPC analysis.
[0313] GPC analysis:
[0314] Solutions of test substances and molecular weight calibration standards were analyzed using the following conditions:
[0315] Chromatographic column: Waters 2695 equipped with Waters column heater module.
[0316] Columns: Four 7.8mm ID X 300mm Styragel columns: HR1+HR2+HR3+HR4 (Waters), connected in series
[0317] Temperature: 35℃
[0318] Mobile phase: THF (Baker Analyzed, HPLC solvent, low in water), 1 mL / min, isocratic
[0319] Injection volume: 25 μL
[0320] Run time: 50min
[0321] Detector: Waters 410 differential refractometer
[0322] Sampling rate: 1
[0323] Temperature: 35℃
[0324] Filter time: 1
[0325] Sensitivity: 4
[0326] Polarity: +ve
[0327] Waters Empower Software, Build 2154 was used for data acquisition and data processing.
[0328] UV Curing of Urethane Acrylates
[0329] Cured samples of urethane acrylates were prepared by blending the urethane acrylates with 10 wt% of the photoinitiator ESACURE KTO 46 (IGM Resins) and rapid mixing at 2000 rpm for 2 minutes. The urethane acrylate / photoinitiator blends were heated to 55°C in an oven to reduce the viscosity, allowing them to be poured into 2 mm deep HDPE molds. The molded resins were then cured by passing the samples through a conveyor system under UV light generated under the following conditions:
[0330] UV Source:
[0331] Innovative Machines Mercury 200W / in, 10ft / min, 4A, 1200V
[0332] Distance from sample to light – 50mm
[0333] Conveyor speed – 10ft / min.
[0334] Irradiance according to EIT Power Puck II S / N 11178:
[0335]
[0336] Dynamic Mechanical Analysis (DMA)
[0337] UV cured urethane acrylate castings were cut into the size of 30 mm x 7 mm x 2 mm (± 0.5 mm) bars. Data were collected on a TA Instruments Q800 DMA in stretched film mode from -90°C to 100°C at a ramp rate of 3°C / min and a frequency of 1 Hz. Tan δ was plotted as a function of temperature and the glass transition temperature was measured at the maximum tan δ value.
[0338] Preparation of adhesive
[0339] Using Hauschild Engineering's double asymmetric centrifugal FlackTek DAC400FVZ All formulations were mixed using the following procedure.
[0340] The ingredients listed in Tables 3 and 4 were used to prepare the inventive and comparative samples.
[0341]
[0342]
[0343]
[0344] Part A Procedure
[0345] 1. THFMA was added to the reactor with Clearstrength core shell rubber and Dymalink, and the mixture was mixed and then rapid mixed at 2,100 rpm for 3 minutes.
[0346] 2. Add the rest of the THFMA and mix and then speed mix at 2,100 rpm for 2 minutes. Add CHMA and half of the Cab-O-Sil. Mix the mixture at 2,100 rpm for 1 minute.
[0347] 3. Add half of Toughener 1 or Urethane Methacrylate (CN1967 / CN1970). Mix the mixture at 2,100 rpm for 2 minutes. Scrape down the sides. Add the rest of Toughener 1 or Urethane Methacrylate and mix at 2100 rpm for 2 minutes
[0348] 4. Add wollastonite and talc fillers and mix at 2100 rpm for 2 minutes.
[0349] 5. Add SR9036A and continue mixing at 2,100 rpm for 2 minutes.
[0350] 6. Add HEMA phosphate, Dynasylan 6498 and methacrylic acid and continue mixing at 2,100 rpm for 2 minutes.
[0351] 7. Add N,N-dimethyltoluidine and glass beads and continue mixing at 800 rpm for 25 seconds followed by 1 minute at 2,000 rpm. Scrape down the sides of the container and repeat the mixing cycle.
[0352] 8. The mixture was mixed at 30 mbar vacuum and 1,800 rpm for 3 minutes.
[0353] Part B Procedure
[0354] 1. Prepare stabilizer pre-blend (1 wt% BHT in DER 331): Add epoxy resin and BHT to reaction vessel. Heat mixture to 90°C and hold for 1 hour to dissolve BHT. Allow vessel to cool to 70°C and then rapid mix at 2,100 rpm for 2 minutes.
[0355] 2. Add stabilizer pre-blend (1 wt% BHT in DER 331), epoxy resin and filler and mix the mixture at 2,100 rpm for 2 minutes.
[0356] 3. Scrape down the sides and then continue mixing at 2,100 rpm for 2 minutes. Allow the mixture to cool to room temperature.
[0357] 4. Add peroxide and continue mixing at 800 rpm for 25 seconds and 2,000 rpm for 1 minute. Scrape down the sides and repeat the mixing cycle. Mix the mixture at 30 mbar vacuum and 1,800 rpm for 3 minutes.
[0358] Impact peel test
[0359] Impact testing was performed with an Instron CEAST Crush Tower according to ISO 11343. Specimens were prepared using electrogalvanized steel, cleaned with acetone and then 2 Oiled with Oest Platinol B 804 / 3COW-1 metal forming lubricant. Part A and Part B of the adhesive were mixed in a weight ratio of 3:1 and hand mixed in a bag for 1 minute. The bonding area was 20X 30mm with a 10 mil bond gap. The bonded samples were cured at 23°C for 1 day and then at 190°C for 45 minutes. The high temperature phase is designed to simulate electrophoretic coating conditions to which such adhesives would likely be exposed.
[0360] As described in the ISO11343 test method, the sample was bolted to the load cell and a moving wedge was inserted. A crosshead with a 50 lb weight attached was dropped from a fixed height at a speed of 6.7 ft / s. The cleavage force was measured and converted to N / mm of the bond line. The results are listed in Table 5.
[0361]
[0362] 1. CF = Cohesive Failure
[0363] 2. BRIT = Brittle Failure
[0364] It is clear from the results that the comparative samples using conventional toughening agents (eg, CN1967 and CN1970) exhibited unacceptably low impact peel strength and brittle failure, making them unsuitable for use. The inventive samples exhibited excellent impact peel strength and only cohesive failure.
[0365] Also noteworthy is the fact that the samples of the present invention exhibit excellent impact peel strength even after high temperature exposure used to simulate electrophoretic coating curing conditions. Acrylic adhesives typically cannot withstand such conditions.
[0366] Lap shear test
[0367] Lap shear specimens were prepared and tested according to ISO standard ISO 4587. The substrate used was 0.8 mm thick electro-galvanized steel supplied by ACT Laboratories, Inc. The test specimens were cut into 1 x 4 inch strips. The 1 / 2 inch bond overlap section of each specimen was cleaned with acetone and then 2 of weight were oiled with Oest Platinol B 804 / 3COW-1 metal forming lubricant. The two components of the adhesive were combined in a 3:1 [Part A:Part B] weight ratio and hand mixed in a bag for 1 minute. The adhesive was applied to the bonded section of the specimen. Another specimen was laid on top and the specimens were assembled in a fixture, creating a 1 / 2 inch overlap. The edges of the assembly were scraped clean using a spatula and held together with binder clips while curing at room temperature for 24 hours, followed by oven baking at 190°C (metal temperature) for 45 minutes. The high temperature phase is designed to simulate electrophoretic coating conditions to which such an adhesive would likely be exposed. Use 5500R material testing system (Instron Corporation) measures the failure load of lap shear at room temperature.Use mechanical clamps to keep the lap shear sample in place.The distance between the clamps is seven inches.The crosshead speed is 0.5in. / min.The computer measures the load that changes with the crosshead displacement, and the load is converted into pounds force / square inch bonding area.After each lap shear test fails, the failure mode is specified by visual assessment.The failure mode is classified as adhesive failure or cohesive failure, and the percentage is specified.The results are listed in Table 6.
[0368]
[0369] 1. TFCF = Thin Film Cohesive Failure. The adhesive still remains on both sides of the substrate, but the adhesive layer after failure is much thinner on one side of the substrate than the other side.
[0370] The results in Table 6 show that the inventive samples exhibited good lap shear strength and were comparable to the comparative samples. Together with the results in Table 5, these results show that the inventive samples achieved excellent impact peel strength and good lap shear strength. This combination of features is not easily achieved with acrylic adhesives when subjecting them to electrophoretic coating conditions (high temperatures >180°C). Electrophoretic coating is performed in the final stages of automotive manufacturing and it is necessary that the adhesive be able to maintain its impact peel strength and lap shear strength after exposure to electrophoretic coating conditions.
Claims
1. A two-component epoxy-acrylic hybrid adhesive comprising: Part A ai) at least one methacrylate monomer; aii) at least one having a T of 0°C or less g A methacrylate-terminated toughening agent; aiii) a phosphorus-containing compound selected from the group consisting of monoesters of phosphonic acid, monoesters and diesters of phosphonic acid and monoesters and diesters of phosphoric acid having one unit in which vinyl or allylic unsaturation is present; aiv) tertiary amine free radical initiator; Part B bi) at least one epoxy resin; bii) Oxidizing agents.
2. A method for bonding two or more substrates, the method comprising the steps of: (1) A two-component epoxy hybrid adhesive is provided, comprising: Part A ai) at least one methacrylate monomer; aii) at least one having a T of 0°C or less g A methacrylate-terminated toughening agent; aiii) a phosphorus-containing compound selected from the group consisting of monoesters of phosphonic acid, monoesters and diesters of phosphonic acid and monoesters and diesters of phosphoric acid having one unit in which vinyl or allylic unsaturation is present; aiv) tertiary amine free radical initiator; Part B bi) at least one epoxy resin; bii) oxidizing agents; (2) mixing Part A and Part B to obtain an adhesive mixture; (3) applying the adhesive mixture to the first substrate, the second substrate, or both; (4) bonding the first substrate and the second substrate into contact with each other; as well as (5) Curing the adhesive mixture.
3. As claimed in claim 1 or 2, wherein: The at least one toughening agent has a T of -20°C or less when measured by DMA. g .
4. As claimed in claim 1, 2 or 3, wherein The toughening agent has a T of -40°C or less when measured by DMA. g .
5. A method as claimed in any preceding claim, wherein: The at least one toughening agent comprises or consists of a toughening agent prepared by reacting a polyether polyol with a polyisocyanate followed by end-capping with a hydroxyalkyl methacrylate.
6. A method as claimed in any preceding claim, wherein: The at least one methacrylate monomer (ai) comprises molecules having the general structure of Formula I: Wherein R is an organic group.
7. A method as claimed in any preceding claim, wherein: Part A additionally comprises one or more divalent metal salts of methacrylic acid, preferably zinc dimethacrylate.
8. As claimed in claim 6, wherein R is selected from H, C1-C2 which may contain one or more heteroatoms 18 A substituted or unsubstituted cyclic or non-cyclic aliphatic hydrocarbon group, and a C4-C 18 Aromatic hydrocarbon group.
9. As claimed in claim 6, wherein R is selected from C1-C 18 Substituted or unsubstituted cyclic or non-cyclic aliphatic hydrocarbon group, in particular, R is cyclohexyl or CH2-THF, wherein THF is 2- or 3-tetrahydrofurfuryl.
10. A method as claimed in any preceding claim, wherein: Part A comprises two or more methacrylate monomers.
11. A method as claimed in any preceding claim, wherein: The at least one methacrylate monomer comprises tetrahydrofurfuryl methacrylate.
12. A method as claimed in any preceding claim, wherein: The at least one methacrylate monomer includes cyclohexyl methacrylate.
13. A method as claimed in any preceding claim, wherein: Part A additionally comprises a divalent metal salt of methacrylic acid, in particular zinc dimethacrylate.
14. A method as claimed in any preceding claim, wherein: The at least one methacrylate monomer includes tetrahydrofurfuryl methacrylate and cyclohexyl methacrylate.
15. A method as claimed in any preceding claim, wherein: The at least one methacrylate monomer includes tetrahydrofurfuryl methacrylate and cyclohexyl methacrylate.
16. A method as claimed in any preceding claim, wherein: The one or more methacrylate monomers represent 25-35 wt %, based on the total weight of part A, more preferably 28-32 wt % of tetrahydrofurfuryl methacrylate.
17. A method as claimed in any preceding claim, wherein: Part A comprises 25-35 wt%, more preferably 28-32 wt%, of tetrahydrofurfuryl methacrylate based on the total weight of Part A.
18. A method as claimed in any preceding claim, wherein: Part A comprises 2-10 wt%, more preferably 3-6 wt%, of cyclohexyl methacrylate based on the total weight of Part A.
19. A method as claimed in any preceding claim, wherein: Part A comprises 0.5-4 wt %, more preferably 0.75-1.5 wt %, of a divalent metal salt of methacrylic acid based on the total weight of Part A.
20. A method as claimed in any preceding claim, wherein: Part A comprises 0.5-4 wt %, more preferably 0.75-1.5 wt %, based on the total weight of Part A, of zinc dimethacrylate.
21. A method as claimed in any preceding claim, wherein: Part A comprises 25-35 wt%, more preferably 28-32 wt%, of tetrahydrofurfuryl methacrylate, and 2-10 wt%, more preferably 3-6 wt%, of cyclohexyl methacrylate, based on the total weight of part A.
22. A method as claimed in any preceding claim, wherein: Part A comprises 25-35 wt%, more preferably 28-32 wt% of tetrahydrofurfuryl methacrylate, 2-10 wt%, more preferably 3-6 wt% of cyclohexyl methacrylate, and 0.5-4 wt%, more preferably 0.75-1.5 wt% of zinc dimethacrylate based on the total weight of Part A.
23. A method as claimed in any preceding claim, wherein: The polyether polyol used to prepare the toughening agent is a diol or a triol.
24. A method as claimed in any preceding claim, wherein: The polyether polyol used to prepare the toughening agent is a diol.
25. A method as claimed in any preceding claim, wherein: The polyether polyol used to prepare the toughening agent is a poly(C2-C6-alkylene oxide) glycol, of which C2, C3 and C4 are preferred, and C4 is particularly preferred [ie poly(tetramethylene oxide) glycol or PTMEG].
26. A method as claimed in any preceding claim, wherein: The polyether polyol used to prepare the toughening agent is selected from PTMEG having a molecular weight of 1,000 to 3,000 Da, more preferably 2,000 Da.
27. A method as claimed in any preceding claim, wherein: The polyisocyanate used to prepare the toughening agent is aliphatic or aromatic.
28. A method as claimed in any preceding claim, wherein: The polyisocyanate used to prepare the toughening agent is aliphatic.
29. A method as claimed in any preceding claim, wherein: The polyisocyanate used to prepare the toughening agent is a diisocyanate.
30. A method as claimed in any preceding claim, wherein: The polyisocyanate used to prepare the toughening agent is selected from hexamethylene diisocyanate (HDI), isophorone diisocyanate and methylene dicyclohexyl diisocyanate.
31. A method as claimed in any preceding claim, wherein: The polyether polyol used to prepare the toughening agent is PTMEG, and the polyisocyanate is HDI.
32. A method as claimed in any preceding claim, wherein: The hydroxyalkyl methacrylate used to prepare the toughening agent is a C2-C6-hydroxyalkyl ester.
33. A method as claimed in any preceding claim, wherein: The hydroxyalkyl methacrylate used to prepare the toughening agent is a C2-C4-hydroxyalkyl ester.
34. A method as claimed in any preceding claim, wherein: The hydroxyalkyl methacrylate used to prepare the toughening agent is a C2-C3-hydroxyalkyl ester.
35. A method as claimed in any preceding claim, wherein: The hydroxyalkyl methacrylate used to prepare the toughening agent is hydroxyethyl methacrylate, i.e. HEMA):
36. A method as claimed in any preceding claim, wherein: The toughening agent has the general formula II: where x has values from 13 to 42.
37. As claimed in claim 36, wherein x is 27.
8.
38. As claimed in claim 36 or 37, wherein y has a value from 1.5 to 5.
39. A method as claimed in any one of claims 36 to 38, wherein: y has a value between 1.8 and 4.
9.
40. Any one of claims 36 to 39, wherein: y is 2.
6.
41. Any preceding claim, wherein: The toughening agent has the general formula II and has a number average molecular weight (M) of 6,119 Da. n ), as determined by gel permeation chromatography (GPC) according to the method described in the Examples section.
42. Any preceding claim, wherein: The toughening agent has the general formula II and has a weight average molecular weight (M w ), as determined by gel permeation chromatography (GPC) according to the method described in the Examples section.
43. Any preceding claim, wherein: Part A comprises 10-30 wt% of a toughening agent (aii) based on the total weight of Part A.
44. Any preceding claim, wherein: Part A comprises 15-25 wt% of a toughening agent (aii) based on the total weight of Part A.
45. Any preceding claim, wherein: Part A comprises 17-22 wt% of a toughening agent (aii) based on the total weight of Part A.
46. Any preceding claim, wherein: The phosphorus-containing compound (aiii) has formula III, IV and V: wherein W are the same or different and each W is independently selected from H and a divalent organic group, wherein at least one W is a divalent organic group, and at least one X is vinyl, and the other X is vinyl or absent (in the case where W is H), or H.
47. Any preceding claim, wherein: The phosphorus-containing compound (aiii) has Formula V.
48. Any preceding claim, wherein: The phosphorus-containing compound (aiii) has formula V, and one, two or three X groups are vinyl groups.
49. Any preceding claim, wherein: The phosphorus-containing compound (aiii) has formula V, and one X group is vinyl.
50. Any preceding claim, wherein: The phosphorus-containing compound (aiii) has formula V, and one, two or three WX groups have formula VI: The dots represent the points of free radical attachment.
51. As claimed in claim 50, wherein One or two WX groups have formula VI, and the remaining WX groups are H.
52. Any preceding claim, wherein: The phosphorus-containing compound comprises a molecule of formula VII:
53. Any preceding claim, wherein: The phosphorus-containing compound comprises a molecule of Formula VIII:
54. Any preceding claim, wherein: The phosphorus-containing compound (aiii) is an approximately 2:1 mixture of Formula VII and Formula VIII.
55. Any preceding claim, wherein: The tertiary amine free radical initiator is N,N-dimethyl-p-toluidine.
56. Any preceding claim, wherein: The at least one epoxy resin comprises a diglycidyl ether of a polyphenol compound.
57. Any preceding claim, wherein: The at least one epoxy resin comprises the reaction product of bisphenol A and epichlorohydrin.
58. Any preceding claim, wherein: The at least one epoxy resin comprises a liquid reaction product of bisphenol A and epichlorohydrin.
59. Any preceding claim, wherein: The at least one epoxy resin comprises a liquid reaction product of epichlorohydrin and bisphenol A, the liquid reaction product having an epoxy equivalent weight of 182-192 g / equivalent (as measured according to ASTM D-1652), an epoxy percentage of 22.4%-23.6% (as measured according to ASTM D-1652), an epoxy group content of 5,200-5,500 mmol / kg (as measured according to ASTM D-1652), and a viscosity of 11,000-14,000 mPas at 25° C. (as measured according to ASTM D-445).
60. Any preceding claim, wherein: The at least one epoxy resin comprises a bisphenol A-based epoxy resin having an epoxy equivalent weight of about 352.5 g / equivalent.
61. Any preceding claim, wherein: The at least one epoxy resin comprises a mixture of a liquid reaction product of epichlorohydrin and bisphenol A and a bisphenol A-based epoxy resin with an epoxy equivalent weight of about 352.5 g / equivalent, the liquid reaction product having an epoxy equivalent weight of 182-192 g / equivalent (as measured according to ASTM D-1652), an epoxy percentage of 22.4%-23.6% (as measured according to ASTM D-1652), an epoxy group content of 5,200-5,500 mmol / kg (as measured according to ASTM D-1652), and a viscosity of 11,000-14,000 mPas at 25° C. (as measured according to ASTM D-445).
62. Any preceding claim, wherein: The at least one epoxy resin comprises 50-90 wt%, more preferably 60-80 wt%, based on the total weight of the epoxy resins in part B, of a liquid reaction product of epichlorohydrin and bisphenol A, the liquid reaction product having an epoxy equivalent weight of 182-192 g / equivalent (as measured according to ASTM D-1652), an epoxy percentage of 22.4%-23.6% (as measured according to ASTM D-1652), an epoxy group content of 5,200-5,500 mmol / kg (as measured according to ASTM D-1652), and a viscosity of 11,000-14,000 mPas at 25° C. (as measured according to ASTM D-445).
63. Any preceding claim, wherein: The at least one epoxy resin comprises 10-50 wt%, more preferably 20-40 wt%, based on the total weight of the epoxy resins in Part B, of a bisphenol A-based epoxy resin having an epoxy equivalent weight of about 352.5 g / equivalent.
64. Any preceding claim, wherein: The at least one epoxy resin comprises, based on the total weight of the epoxy resins in part B, 50-90 wt%, more preferably 60-80 wt%, of a liquid reaction product of epichlorohydrin and bisphenol A and 10-50 wt%, more preferably 20-40 wt%, of a bisphenol A-based epoxy resin having an epoxy equivalent weight of about 352.5 g / equivalent, the liquid reaction product having an epoxy equivalent weight of 182-192 g / equivalent (as measured according to ASTM D-1652), an epoxy percentage of 22.4%-23.6% (as measured according to ASTM D-1652), an epoxy group content of 5,200-5,500 mmol / kg (as measured according to ASTM D-1652), and a viscosity of 11,000-14,000 mPas at 25° C. (as measured according to ASTM D-445).
65. Any preceding claim, wherein: Part B comprises at least one epoxy resin in an amount of 20 to 80 wt %, more preferably 20 to 60 wt %, very particularly preferably 25 to 40 wt %, based on the total weight of part B.
66. Any preceding claim, wherein: The oxidizing agent is an organic peroxide.
67. Any preceding claim, wherein: The oxidant is selected from benzoyl peroxide and other diacyl peroxides, hydroperoxides such as cumene hydroperoxide, peresters such as β-butyl peroxybenzoate; ketone hydroperoxides such as methyl ethyl ketone hydroperoxide, organic salts of transition metals such as cobalt naphthenate, and labile chlorine-containing compounds such as sulfonyl chloride.
68. Any preceding claim, wherein: The organic peroxide is benzoyl peroxide.
69. Any preceding claim, wherein: The organic peroxide is present in part B at 3-10 wt %, based on the total weight of part B, more preferably 5-9 wt %.
70. Any preceding claim, wherein: Part B comprises 3-10 wt %, more preferably 5-9 wt %, of benzoyl peroxide based on the total weight of Part B.
71. Any preceding claim, wherein: Part A and / or part B comprises a stabilizer and / or a free radical stabilizer.
72. Any preceding claim, wherein: Part A and / or part B comprises a stabilizer and / or a free radical scavenger selected from 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, diethylhydroxylamine (DEHA), butylated hydroxytoluene (BHT) and mixtures of these.
73. Any preceding claim, wherein: Part A and / or part (B) comprises a filler selected from wollastonite, talc, fumed silica, calcium carbonate and mixtures of these.
74. Any preceding claim, wherein: Part A contains additional toughening agents.
75. Any preceding claim, wherein: Part A comprises an additional toughening agent, which is rubber-based, such as acrylate-based toughening agents, butadiene-based toughening agents, acrylonitrile-butadiene-based toughening agents, chlorinated or chlorosulfonated polyethylene, block copolymers of styrene and conjugated dienes (SBS, SIS), ethylene acrylic elastomers, core-shell graft copolymers.
76. Any preceding claim, wherein: Part A additionally comprises a rubber-based toughening agent.
77. Any preceding claim, wherein: Part A additionally comprises a rubber-based toughener selected from acrylate-based tougheners, butadiene-based tougheners, acrylonitrile-butadiene-based tougheners, chlorinated or chlorosulfonated polyethylene, block copolymers of styrene and conjugated dienes (SBS, SIS), ethylene acrylic elastomers, core-shell graft copolymers.
78. Any preceding claim, wherein: Part A additionally comprises a rubber-based toughening agent which is a copolymer of methyl 2-methyl-2-acrylate and 1,3-butadiene.
79. Any preceding claim, wherein: The additional rubber-based toughening agent is used in part A at 2-24 wt %, based on the total weight of part A, more preferably 7.5-18.5 wt %, very particularly preferably 10-15.75 wt %.
80. Any preceding claim, wherein: Part A additionally comprises a rubber-based toughening agent, which is used in an amount of 2-24 wt %, based on the total weight of part A, more preferably 7.5-18.5 wt %, very particularly preferably 10-15.75 wt %.
81. Any preceding claim, wherein: Part A additionally comprises a rubber-based toughener, which is selected from acrylate-based tougheners, butadiene-based tougheners, acrylonitrile-butadiene-based tougheners, chlorinated or chlorosulfonated polyethylene, block copolymers of styrene and conjugated dienes (SBS, SIS), ethylene acrylic elastomers, core-shell graft copolymers, and is used in an amount of 2-24 wt%, more preferably 7.5-18.5 wt%, and more particularly preferably 10-15.75 wt%, based on the total weight of part A.
82. Any preceding claim, wherein: Part A comprises a rubber-based toughening agent which is a copolymer of methyl 2-methyl-2-acrylate and 1,3-butadiene, used at 2-24 wt %, more preferably 7.5-18.5 wt %, more particularly preferably 10-15.75 wt %, based on the total weight of Part A.